Paternalism and equality - Voigt, K (Springer, 2015)
Paternalistic interventions restrict individuals’ liberty or autonomy so as to guide their decisions towards options that are more beneficial for them than the ones they would choose in the absence of such interventions. Although some philosophers have emphasised that there is a case for justifiable paternalism in certain circumstances, much of contemporary moral and political philosophy works from a strong presumption against paternalistic interventions. However, Richard Arneson has argued that there are egalitarian reasons that support the case for paternalism: paternalistic interventions can protect poor decision-makers from making ‘bad’ choices, thus preventing inequalities between them and those with better decision-making skills. This paper seeks to clarify and advance our understanding of the egalitarian argument for paternalism. Arneson’s argument adds an important and often neglected dimension to the debate about paternalism but also raises a number of questions about equality, paternalism and the relationship between the two.